ASSOCIATION BETWEEN PLACENTAL ABRUPTION AND CAESAREAN SECTION AMONG PATIENTS AT KHYBER TEACHING HOSPITAL PESHAWAR - Gul, Seema; Abrar, Saidul; Jamal, Tanveer; Rana, Gul e; Majid, Anam; Iqbal, Madiha (Journal of Ayub Medical College Abbottabad, 2016)
Background: Ante partum haemorrhage remains to be a major cause of morbidity and mortality.30% of this haemorrhage is attributed to placental abruption. Along with other adverse maternal outcomes, it increases the risk of Caesarean sections in patients, which is a public health concern. This study was conducted to find out whether any significant association exists between placental abruption and C-section in our set up. Methods: A cross-sectional study was conducted from July 26th, 2011 to May 1st, 2013 (i.e., 21 months) in the Department of Obstetrics and Gynaecology, Khyber Teaching Hospital Peshawar on a sample of 334 patients who presented with antepartum haemorrhage after 28 weeks of gestation. All those patients with and without placental abruption were followed throughout pregnancy and labour to detect the risk of caesarean section. Results: Among study participants, parity had the highest dispersion while gestational age had the lowest. Caesarean section was performed on 26.3% (95% CI) of the study participants. Proportion of placental abruption among patients presenting with ante partum haemorrhage was 20.6%, (95% CI) out of which 7.5% underwent C-section. Association between placental abruption and C-section was found significant at Î±=0.05 (p=0.03). Conclusion: Risk of caesarean section is increased in pregnancies complicated by placental abruption as compared to pregnancies complicated by other causes of ante partum haemorrhage.